Analysis of Shopee PayLater Acceptance Using The Technology Acceptance Model (TAM) Among Students at Indragiri Islamic University - Riska; Usman (STMIK Methodist Binjai, 2026)
Buy now pay later services such as Shopee PayLater are increasingly being adopted by university students as a digital payment alternative, even though this phenomenon often collides with consumptive behavior and the low financial literacy of its users. This study aims to analyze the acceptance level of Shopee PayLater usage among students at Universitas Islam Indragiri by applying the Technology Acceptance Model (TAM) framework. This quantitative research utilizes primary data collected from 89 student respondents through a purposive sampling technique. The data were analyzed through multiple linear regression using IBM SPSS Statistics to test the significance of the Perceived Usefulness (PU), Perceived Ease of Use (PEOU), and Attitude (ATT) variables on the intention to use or Behavioral Intention (BI). Based on the statistical test results, it was found that perceived usefulness (PU) and perceived ease of use (PEOU) do not have a partially significant effect on the intention to use the service. Conversely, the attitude (ATT) variable proved to have a positive and the most significant influence on students' behavioral intention. Simultaneous testing confirmed that the three independent variables collectively influence the intention to use, with the regression model capable of explaining 74.6% of the total variance (R² = 0.746). The conclusion of this study asserts that user attitude plays a crucial role and serves as the most dominant determining factor in driving students to continue utilizing the Shopee PayLater service, outweighing considerations regarding the usefulness and ease of the application itself